Next Generation Users: Changing Access to the Internet - Blank, Grant; Dutton, William H. (AoIR Selected Papers of Internet Research, 2013)
We investigate some implications of the rising use of mobile devices and multiple devices to access the Internet. Next Generation Users are defined as Internet users who access the Internet (1) on mobile devices and (2) on multiple devices. Data from the 2011 Oxford Internet Survey shows that Next Generation Users are disproportionately likely to use the Internet for entertainment, content production, and information-seeking. Logistic regression shows that Next Generation Users tend to be younger, wealthier, have positive attitudes toward technology and to have used the Internet longer. We conclude that mobility and multiple devices are reconfiguring their access to information, people and services in ways that are likely to empower them in relation to other users. This may herald the beginning of a new digital divide.